2004
DOI: 10.1159/000078015
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization and physical mapping of three cervid satellite DNA families in the genome of the Formosan muntjac <i>(Muntiacus reevesi micrurus)</i>

Abstract: Due to their high sequence diversity even among closely related species, satellite DNA sequences can be a useful molecular marker for phylogenetic and taxonomic analyses. To characterize the satellite DNA in the genome of a native muntjac species of Taiwan, the Formosan muntjac, satellite DNA clones representing three different cervid satellite DNA families from this species were isolated and analyzed. Genomic organization study of these satellite DNAs was also undertaken. Three Formosan muntjac satellite DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…1a). When BMC5 clone was aligned with FM-sat I clone (M. reevesi micrurus satellite I clone) (Lin et al, 2004), 88% similarity was found between nucleotides 1-437 of BMC5 clone and nucleotides 775-1211 of FM-sat I clone, and there was also a 91% similarity between nucleotides 26-437 of BMC5 clone and nucleotides 4-416 of FM-sat I clone (Fig. 1b).…”
Section: Molecular Cloning and Characterization Of Satellite I Ii Imentioning
confidence: 95%
See 3 more Smart Citations
“…1a). When BMC5 clone was aligned with FM-sat I clone (M. reevesi micrurus satellite I clone) (Lin et al, 2004), 88% similarity was found between nucleotides 1-437 of BMC5 clone and nucleotides 775-1211 of FM-sat I clone, and there was also a 91% similarity between nucleotides 26-437 of BMC5 clone and nucleotides 4-416 of FM-sat I clone (Fig. 1b).…”
Section: Molecular Cloning and Characterization Of Satellite I Ii Imentioning
confidence: 95%
“…BM700 is 667 bp in length and had 62.37% GC content, and FM700 had a length of 660 bp and 63.03% GC content. Nucleotides 242-634 of BM700 clone had 84% similarity with nucleotides 141-533 of FM-sat II clone (M. reevesi micrurus satellite II clone) (Lin et al, 2004), and nucleotides 1-195 had 74% homology with nucleotides 619-817 of FM-sat II, and nucleotides 242-543 of BM700 was of 81% similarity with nucleotides 843-1143 of FM-sat II clone (Fig. 2b).…”
Section: Molecular Cloning and Characterization Of Satellite I Ii Imentioning
confidence: 96%
See 2 more Smart Citations
“…Cell lines, chromosome preparations, and DNA isolation Metaphase chromosome spreads and genomic DNAs were prepared from the fibroblast cell lines of the following species: Indian muntjac (Muntiacus muntjak vaginalis) (male cell line, CCL-157, American Type Culture Collection; female cell line, kindly supplied by Dr. Andrew P. Feinberg, School of Medicine, Johns Hopkins University, Baltimore, MD, USA); Formosan muntjac (M. reevesi micrurus) ; caribou (Rangifer tarandus caribou) (Lin et al 1991;Lee et al 1994;Lin et al 2004); male black-tailed deer (Odocoileus hemionus hemionus) (CRL-6193, American Type Culture Collection); female Chinese water deer (Hydropotes inermis) (kindly provided by Dr. F. Yang, Centre for Veterinary Science, University of Cambridge, Cambridge, UK); Roe deer (Capreolus capreolus capreolus) cell line (from San Diego Zoo, San Diego, CA, USA) and male Formosan sambar deer (Cervus unicolor swinhoei) (Li et al 2005). Metaphase chromosome spreads and genomic DNAs of Formosan sika (Cervus nippon taioanus) and Asian red deer (Cervus elaphus) were prepared from blood samples provided by a certified deer farm in Taiwan.…”
Section: Methodsmentioning
confidence: 99%